Ingestion rate of postlarvae Penaeus monodon fed Apocyclops dengizicus and Artemia - Farhadian, Omidvar; Md Yusoff, Fatimah; Arshad, Aziz (Elsevier, 2007)

(untitled)
Three different live diets including; Apocyclops copepodids, Artemia nauplii, and combination of Apocyclops copepodids and Artemia nauplii were offered to two groups of Penaeus monodon larvae viz PL3–6 and PL9–12. The prey diets were offered to each group at three density levels (6, 13 and 20 μg dry weight/ml). The results showed that PL3–6 P. monodon larvae consumed Apocyclops copepodids (CII–CIV) at 5.1–14.3 ind./day, the Artemia nauplii at 18.4–39.2 ind./day, and mixture of Apocyclops and Artemia at 12.2–41.5 ind./day. Similarly, PL9–12 P. monodon larvae ingested Apocyclops at 12.6–51.7 ind./day, Artemia at 62.4–101.6 ind./day, and their mixture at 48.0–65.3 ind./day. This study indicated that P. monodon larvae, at PL3–6 and PL9–12, can ingest Apocyclops selectively better than Artemia at 1:1 ratio as shown by the improved body dry weight of the larvae.